An Anesthesia Preinduction Checklist to Improve Information Exchange, Knowledge of Critical Information, Perception of Safety, and Possibly Perception of Teamwork in Anesthesia Teams. (October 2015) - Tscholl, David W.; Weiss, Mona; Kolbe, Michaela; Staender, Sven; Seifert, Burkhardt; Landert, Daniel; Grande, Bastian; Spahn, Donat R.; Noethiger, Christoph B.
Abstract : BACKGROUND: An anesthesia preinduction checklist (APIC) to be performed before anesthesia induction was introduced and evaluated with respect to 5 team-level outcomes, each being a surrogate end point for patient safety: information exchange (the percentage of checklist items exchanged by a team, out of 12 total items); knowledge of critical information (the percentage of critical information items out of 5 total items such as allergies, reported as known by the members of a team); team members' perceptions of safety (the median scores given by the members of a team on a continuous rating scale); their perception of teamwork (the median scores given by the members of a team on a continuous rating scale); and clinical performance (the percentage of completed items out of 14 required tasks, e.g., suction device checked). METHODS: A prospective interventional study comparing anesthesia teams using the APIC with a control group not using the APIC was performed using a multimethod design. Trained observers rated information exchange and clinical performance during on-site observations of anesthesia inductions. After the observations, each team member indicated the critical information items they knew and their perceptions of safety and teamwork. RESULTS: One hundred five teams using the APIC were compared with 100 teams not doing so. The medians of the team-level outcome scores in the APIC group versus the control group were as follows: information exchange: 100% vs 33% ( P < 0.001), knowledge of critical information: 100% vs 90% ( P < 0.001), perception of safety: 91% vs 84% ( P < 0.001), perception of teamwork: 90% vs 86% ( P = 0.028), and clinical performance: 93% vs 93% ( P = 0.60). CONCLUSIONS: This study provides empirical evidence that the use of a preinduction checklist significantly improves information exchange, knowledge of critical information, and perception of safety in anesthesia teams—all parameters contributing to patient safety. There was a trend indicating improved perception of teamwork. Abstract : Supplemental Digital Content is available in the text.Published ahead of print March 24, 2015